2018
DOI: 10.1016/j.bjm.2018.04.004
|View full text |Cite
|
Sign up to set email alerts
|

First report of the production of a potent biosurfactant with α,β-trehalose by Fusarium fujikuroi under optimized conditions of submerged fermentation

Abstract: Biosurfactants have many advantages over synthetic surfactants but have higher production costs. Identifying microorganisms with high production capacities for these molecules and optimizing their growth conditions can reduce cost. The present work aimed to isolate and identify a fungus with high biosurfactant production capacity, optimize its growth conditions in a low cost culture medium, and characterize the chemical structure of the biosurfactant molecule. The fungal strain UFSM-BAS-01 was isolated from so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(15 citation statements)
references
References 33 publications
(54 reference statements)
1
13
0
Order By: Relevance
“…The biosurfactant production during logarithmic growth phase and stationary phase of microorganisms have already been studied from various fungal species e.g., A. ustus [42], A. niger [43,44], A. flavus [43,46], A. versicolor [47], and Piper hispidum [48], and various factors influencing the total biosurfactant yield during fermentation have broadly been studied in previous few decades [42,[49][50][51][52][53][54]. From these, several studies have reported classical methods for optimization purpose by placing one factor as constant and modifying another one.…”
Section: Discussionmentioning
confidence: 99%
“…The biosurfactant production during logarithmic growth phase and stationary phase of microorganisms have already been studied from various fungal species e.g., A. ustus [42], A. niger [43,44], A. flavus [43,46], A. versicolor [47], and Piper hispidum [48], and various factors influencing the total biosurfactant yield during fermentation have broadly been studied in previous few decades [42,[49][50][51][52][53][54]. From these, several studies have reported classical methods for optimization purpose by placing one factor as constant and modifying another one.…”
Section: Discussionmentioning
confidence: 99%
“…The chemical nature of the biosurfactant produced by B. bassiana (BBLP) is a mixture of lipid and protein (with approximately a 1:4 ratio) [39,[59][60][61]. Impressively, the BBLP exhibited excellent surface active abilities which made it one of the rare fungal based-surfactants that can be effective in reducing surface tension, with respect to bacterial based-surfactants [14,23,62]. Moreover, the data obtained from GC-MS, RP-HPLC, and 1 H NMR analysis ensure the lipopeptide nature of the BBLP and indicates the presence of oleic and palmitic acids as a lipid part; and L-arginine, L-threonine, and L-leucine as the protein part of the biosurfactant ( Figure 3A-C).…”
Section: Discussionmentioning
confidence: 99%
“…erefore, the abovementioned genera are promising producers of biosurfactants and emulsifiers with stable emulsions and have an excellent capacity to reduce surface and interfacial tension [44,49,53,55,59,68].…”
Section: Biosurfactant Production By Ascomycetesmentioning
confidence: 99%
“…Ascomycetes that produce biosurfactants have been obtained from different sources such as plants, soil, and contaminated environments and can produce a variety of biosurfactants in synthetic media or on renewable substrates (Table 1). Additionally, they can be isolated from areas contaminated with oil, effluents, or hydrocarbons [45,53,59,69], which increases the chances of isolating a fungus that produces the compound. However, several studies have demonstrated the isolation of areas such as soil, plants, and in marine environments [42,49,50,61].…”
Section: Biosurfactant Production By Ascomycetesmentioning
confidence: 99%